Benchmarking vehicle and passenger travel characteristics in Delhi for on-road emissions analysis. Issue 2 (May 2015) - Goel, Rahul; Guttikunda, Sarath K.; Mohan, Dinesh; Tiwari, Geetam
Abstract In a mega-city like Delhi, vehicle exhaust emissions play a central role for urban air quality management, and measuring these on-road emissions in an environment with mixed fuels, mixed engine sizes, mixed technologies, and mixed usage patterns, is a challenging task, which means a better understanding of the vehicle and the passenger characteristics in the city is necessary. In this paper, we present a series of survey methods – vehicle owners' interviews at fuel stations, on-road observational studies, and use of data resources like vehicle registrations and pollution under check program, which can be utilized to benchmark parameters linked to an emissions inventory methodology (Activity–Share–Intensity–Factor – ASIF). We present estimates for fuel efficiency, age profiles, annual mileage, and number of in-use vehicles for cars, motorized two-wheelers (2Ws), three-wheeled scooter rickshaws (3Ws), and buses and modeled survival functions for cars and 2Ws using log-logistic distribution function. In addition, using GPS data logging, we evaluated speed distribution of buses, cars, 2Ws and 3Ws, which resulted in evaluating the modal idling times, all of which were utilized to develop a robust vehicle exhaust emissions inventory for Delhi – segregated by vehicle type, fuel type, and age group. The survey methods and analytical techniques are simple and fast to implement, which when replicated, can provide a useful data source to estimate on-road transport emissions in urban areas.